Makna Biaya Dalam Tradisi Antar Harta (Dutu) Dilihat Dari Sudut Pandang Akuntansi - Siti Magfira Rahmatia Lahay; Tri Handayani Amaliah; Ayu Rakhma Wuryandini (STIE Amkop Makassar, 2024)
The results of this research show that the meaning of costs in the